Answer: y=15
Explanation:
Solution for (5y+3)+(4y+8)=146 equation:
Simplifying
(5y + 3) + (4y + 8) = 146
Reorder the terms:
(3 + 5y) + (4y + 8) = 146
Remove parenthesis around (3 + 5y)
3 + 5y + (4y + 8) = 146
Reorder the terms:
3 + 5y + (8 + 4y) = 146
Remove parenthesis around (8 + 4y)
3 + 5y + 8 + 4y = 146
Reorder the terms:
3 + 8 + 5y + 4y = 146
Combine like terms: 3 + 8 = 11
11 + 5y + 4y = 146
Combine like terms: 5y + 4y = 9y
11 + 9y = 146
Solving
11 + 9y = 146
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-11' to each side of the equation.
11 + -11 + 9y = 146 + -11
Combine like terms: 11 + -11 = 0
0 + 9y = 146 + -11
9y = 146 + -11
Combine like terms: 146 + -11 = 135
9y = 135
Divide each side by '9'.
y = 15